Day and Night GSH and MDA Levels in Healthy Adults and Effects of Different Doses of Melatonin on These Parameters - Shilpa Chakravarty; Syed Ibrahim Rizvi (International Journal of Cell Biology)
The pineal secretory product melatonin (chemically, N-acetyl-5-methoxytryptamine) acts as an effective antioxidant and free-radical scavenger and plays an important role in several physiological functions such as sleep induction, immunomodulation, cardiovascular protection, thermoregulation, neuroprotection, tumor-suppression and oncostasis. Membrane lipid-peroxidation in terms of malondialdehyde (MDA) and intracellular glutathione (GSH) is considered to be a reliable marker of oxidative stress. The present work was undertaken to study the modulating effect of melatonin on MDA and GSH in human erythrocytes during day and night. Our observation shows the modulation of these two biomarkers by melatonin, and this may have important therapeutic implications. In vitro dose-dependent effect of melatonin also showed variation during day and night. We explain our observations on the basis of melatonin's antioxidative function and its effect on the fluidity of plasma membrane of red blood cells. Rhythmic modulation of MDA and GSH contents emphasized the role of melatonin as an antioxidant and its function against oxidative stress.